AI Sovereignty at Universities: Defending Academic Freedom in the Age of Algorithms - Salden, Peter (International Higher Education, 2025)
<main class="pub-body-component"> <h3 id="the-question-of-digital-sovereignty-is-becoming-more-urgent-for-universities-in-the-age-of-ai-ai-based-applications-are-not-only-critical-from-the-perspective-of-data-protection-and-functional-transparency-but-also-pose-a-threat-to-independent-thinking-ai-literacy-an-independent-ai-infrastructure-and-a-clearly-defined-strategic-framework-are-fundamental-for-defending-academic-freedom">The question of digital sovereignty is becoming more urgent for universities in the age of AI. AI-based applications are not only critical from the perspective of data protection and functional transparency, but also pose a threat to independent thinking. AI literacy, an independent AI infrastructure, and a clearly defined strategic framework are fundamental for defending academic freedom. </main>